A inserção dos docentes ingressantes no contexto da EPT: um estudo de caso em um Instituto Federal da região Norte do Brasil - Costa, Efraim Menezes de Lima (2022)
The process of inserting teachers into new teaching contexts is a peculiar moment in the lives of teachers. From the formative point of view, it represents a link between initial and continuing education, representing professional induction. When this context is within professional and technological education within the Amazon region, due to its conceptual basis and objectives, it becomes even more peculiar the afflictions and difficulties of teachers. In view of this, this master's research seeks to discuss the aspects related to the insertion process of teachers of professional and technological education in a federal institute of education, science and technology in the northern region of Brazil, highlighting the formative, experiential and motivational profile of teachers, the measures adopted by the institution in the process of welcoming and inserting them, how this process developed, what were the difficulties encountered and what actions could be implemented to reduce the tensions of this process. For this, the case study strategy was used in the perspective of Yin (2015) to collect the data in the various sources, which are divided into quantitative and qualitative. For the quantitative ones, the survey strategy was adopted, and for the qualitative ones, document analysis and content analysis. The collection instruments were bibliographic and documental references, questionnaires, and interviews with teachers who joined the institution in 2020. As a result, it was created an educational material that aims to support incoming teachers in this moment of entry as a teacher of Basic Technical and Technological Education with a view to the omnilateral training of students since this is one of the founding principles of EFA today, entitled "Handbook for the incoming teacher of IFAM". The research is affiliated to the research line "Organization and Memories in Pedagogical Spaces in Vocational and Technological Education", specifically in macroproject 4 - Stories and Memories in the context of EFA, of the Professional Master's in Vocational and Technological Education (ProfEPT), IFAM pole, Campus Manaus Centro.